Searching for the grey zone in Slovak sci-fi literature during the normalisation period - Olha Norba (Slovenska Literatura)
This article analyses the phenomenon of the grey zone as a space for alternative expression in Slovak literature during the late 1970s and throughout the 1980s. It connects the emergence and expansion of this grey zone to the gradual ideological erosion of the communist system during the late normalisation period. The article locates the expression of social critique within the realm of the sci-fi genre, which allowed authors to escape into fantastical worlds without severing ties to real-world conditions. In conveying their moral concerns, authors employed not only escapist strategies of subversion, but also conformist motifs designed to legitimise their messages within official discourse. The dystopian genre was frequently utilized, characterized by pronounced catastrophism, scepticism, and anti-illusionism. Prominent themes included environmental pollution, warnings against the loss of humanity, calls for peace, fear of nuclear catastrophe, and condemnation of power domination and totalitarian rhetoric. Searching for the grey zone in Slovak sci-fi literature of the normalisation period proved to be an effective way to re-evaluate the traditional black-and-white vision of society, which was viewed as divided into the “fighting dissent” and the masses blindly accepting the ruling regime.